Indigenous Knowledge in Esan Proverbs of Edo State Nigeria (International Journal of Culture and Art Studies, 2023)
The Esan people are an ethnicity in the Edo state of Nigeria. Their language and culture are a subset of the larger Edo ethnic group in Nigeria. A close study of the Esan indigenous knowledge and culture reveals that the appeal of the Esan folk proverbs is in their eclectic nature because of their portrayal of diverse issues in the Esan cosmology and belief system, ranging from folk art to traditional health care beliefs and practices. This finding suggests that the subject of Esan proverbs deserves some scholarly attention. This article, therefore, examines the nature of Esan proverbs even as they perform their didactic and pedagogical functions in contemporary Esan parlance. By its nature, this study adopted a combination of research approaches, which included content analysis, library searches, and ethnographic methods such as interviews and observations. In the ethnographic study of a specific Nigerian with a focus on its proverbs, this paper’s research light shall beam over the five local government areas (LGAs) populated by the Esan people in the Edo State of Nigeria. Apart from its potential for insightful scholarship, the significance of this study on Esan proverbs also lies in the fact that inquiries into the indigenous knowledge system (IKS) portray folk proverbs as veritable windows into the culture and essence of a people. Indigenous knowledge has much more impact on contemporary society than people know.